30 godina članstva Bosne i Hercegovine u Ujedinjenim nacijama: Vitalno, vidljivo, održivo / 30 Years of Membership of Bosnia and Herzegovina in the United Nations: Vital, Visible, Viable - Džananović Miraščija, Nedžma (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
The article is part of a broader research into the diplomatic practice of Bosnia and Herzegovina, especially its positioning in international organizations, the use of rights and obligations arising from international membership for the purpose of realizing the foreign policy goals of the state, as well as the contribution of Bosnia and Herzegovina to the realization of the goals of those organizations. The focus is on the engagement of Bosnia and Herzegovina in a global international organization - the United Nations, over a period of thirty years